1965
DOI: 10.1143/ptp.33.769
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Hamada-Johnston Potential

Abstract: It has been pointed out by Blattll that the Ramada-Johnston potentiaPl would lead to bound two-nucleon 3 LJ-L-olct states with sufficiently high J_ The argument goes as follows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
185
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(194 citation statements)
references
References 0 publications
9
185
0
Order By: Relevance
“…The existence of this scale has been indicated from the sharp falloff of the large angular component of the cosmic microwave background spectrum [44,45,46]. 10 evaluated as ∂ 2 ∂x 2…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of this scale has been indicated from the sharp falloff of the large angular component of the cosmic microwave background spectrum [44,45,46]. 10 evaluated as ∂ 2 ∂x 2…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…5 No coupling constant thus implies that there is no field-renormalization factor. This is one of the most significant proper- 4 This nonrenormalization theorem has been demonstrated explicitly in loop calculations of higher order [10,11,12].…”
Section: Renormalization Procedures and Asymptotic Background Freedommentioning
confidence: 94%
See 1 more Smart Citation
“…In the mathematical literature one can find a general theory for constructing conformal operators [5,6,7,8], which can be used to obtain explicit examples. For instance, the analog of Paneitz operator with six derivatives, ∆ 6 , in D = 6 can be found in [9], consequent paper [10] and in [11], where the generalization to D = 6 was also obtained.…”
Section: Introductionmentioning
confidence: 94%
“…Especially, in Ref. [2], it is shown that the relation between SQG and the 4D conformal gravity [3], calculating with the grand-canonical method.…”
Section: Introduction and Modelmentioning
confidence: 99%